Sir John Franklin's Arctic discoveries, between Baffin Bay & Cape Bathurst, combined with those of Sir Edward Parry in 1819, and the several searching expeditions, concluding with that of Sir Francis L. McClintock in 1859 / constructed by John Arrowsmith (John Arrowsmith, 1860)
Jany 17, 1860 Relief shown by hachures. Inset: Sketch of Bellot Strait by Captn. Allen Young. Color; 1:3,000,000